EMPLOYMENT EXPECTATIONS OF UNDERGRADUATE LEVEL PUBLIC RELATIONS STUDENTS (THE CASE OF PUBLIC UNIVERSITIES and PRIVATE UNIVERSITIES) - E. Fazıl Çöllü (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
The number of enterprises and institutions that recognize the importance of public relations are increasing and the standards of the public relations agencies that are serving to these enterprises and institutions are better of in the Turkish environment which is trying to keep pace with globalization. The existence of some agencies that trace the developments in the world and achieve successful projects is observed in Turkey.However, most of the undergraduate students are facing problems relating to the employment opportunities caused by the lower development level of the sector and high rates of employment from the sectors out of public relations.This study aims to find and compare the expectations and apprehensions of public university and private university undergraduate students studying at the faculty of communication upon their graduation.This research is managed at the Communication Faculties of Selcuk University and Baskent University and there are 100 respondents that are still studying at the faculties from each University.